Diatom silica–titania photocatalysts for air purification by bio-accumulation of different titanium sources. Issue 5 (1st August 2016) - Van Eynde, E.; Hu, Z.-Y.; Tytgat, T.; Verbruggen, S. W.; Watté, J.; Van Tendeloo, G.; Van Driessche, I.; Blust, R.; Lenaerts, S.
Abstract : Diatom microalgae are used to fabricate silica–titania photocatalysts for air purification by means of a biological immobilization process into the diatom frustules. Abstract : We present a green, biological production route for silica–titania photocatalysts using diatom microalgae. Diatoms are single-celled, eukaryotic microalgae (2–2000 μm) that self-assemble soluble silicon (Si(OH)4 ) into intricate silica cell walls, called frustules. These diatom frustules are formed under ambient conditions and consist of hydrated silica with specific 3D morphologies and micro–meso or macroporosity. A remarkable characteristic of diatoms is their ability to bioaccumulate soluble titanium from cell culture medium and incorporate them into their nanostructured silica cell wall. Controlled cultivation of the diatom Pinnularia sp. on soluble titanium in a batch process resulted in the biological immobilisation of titanium dioxide in the porous 3D architecture of the frustules. Six different titanium sources are tested. The silica–titania frustules were isolated by treating the harvested Pinnularia cells with nitric acid (65%) or by high temperature treatment. Thermal annealing converted the amorphous titania into crystalline titania. The produced silica–titania material is evaluated towards photocatalytic activity for acetaldehyde (C2 H4 O) abatement. Frustules cultivated with TiBaldH showed the highest photocatalytic performance. Comparison of the photocatalytic activity with P25 reveals that P25 has a 4 fold higher photocatalytic activity, but when photocatalytic activity is normalized for titania content, the frustules show double activity. Further material characterization (morphology, crystallinity, surface area and elemental distribution) of the TiBaldH silica–titania frustules provides additional insight into their structure–activity relationship. These natural biosilica–titania materials have excellent properties for photocatalytic purposes, including high surface area (108 m 2 g −1 ) and good porosity, and show reliable immobilization of TiO2 in the ordered structure of the diatom frustule.